Phosphate burial in aquatic sediments: Rates and mechanisms of vivianite formation from mackinawite - Mingkai Ma; Peter Overvest; Arjan Hijlkema; Stefan Mangold; Catherine McCammon; Andreas Voegelin; Thilo Behrends (Chemical Engineering Journal Advances, 2023)
Excess phosphorus abundance often drives eutrophication and affects surface water quality. Formation of vivianite (Fe3(PO4)2 • 8H2O) in aquatic sediments acts as a significant sink for phosphate (P), crucial for resorting surface waters. Authigenic vivianite formation, however, can be limited by other ferrous iron containing phases, in particular iron sulfides. Although thermodynamically feasible under suitable conditions, the formation of vivianite from mackinawite has been widely disregarded for authigenic phosphate mineral formation. Here we investigated the formation of vivianite from mackinawite (FeS) in batch experiments in which dissolved sulfide was continuously removed, at P levels between 0 – 5 mM in a pH of 6 to 8. Solid characterizations by electron microscopy, X-ray diffraction as well as Mössbauer and X-ray absorption spectroscopy demonstrates that vivianite was formed at all pH values in P amended experiments. The temporal evolution of dissolved Fe(II) concentrations indicates that the transformation proceeds via the release of the dissolved Fe(II) by FeS dissolution and subsequent vivianite precipitation, over time scales of days. The kinetics of the transformation are controlled by the dissolution rates of FeS. Aging and transformation of FeS, however, compete with vivianite formation. Aging is more pronounced at higher pH but is inhibited by P adsorption. Hence, the effect of pH and P concentration on aging is the main reason for the influence on these parameters on the rates and extent of vivianite formation. Our findings demonstrate that FeS can be an effective iron source for vivianite formation in aquatic sediments when sulfide concentrations decrease due to, for example, changes in external forcing or microbial sulfide oxidation. Formation of vivianite from FeS as an Fe source can also open new perspectives in P recovery in water treatment, for example when Fe is added to digesters to bind H2S.